Peculiarities of post-viral chronic fatigue syndrome associated with mild cognitive decline in patients with atypical chronic active herpesvirus infections - E. O. Khalturina; I. V. Nesterova (Медицинская иммунология)
According to modern ideas, changes in the functioning of the immune system affect the immune processes in the nervous system, contributing to the development of neuro-immuno-inflammation and thereby indirectly affect the rate of progression of neurodegenerative processes. The aim of our study was to investigate the prevalence of post-viral chronic fatigue syndrome and cognitive impairment (aMCI) among patients with atypical, chronic active herpesvirus infections (ACA-HVI).Under our supervision were 126 patients of both sexes aged 18 to 60 years with ACA-HVI.It was established that mono-EBV infection affects 27.7%; mixed EBV infection is observed in 72.3% of patients. When assessing cognitive functioning using CGI, MMSE scales, the incidence of aMCI was found to be 68.3%: with mixed HVI — 87.4%, with mono HVI — 38.8%. During the study, significant limitations were identified in the use of standard scales due to the impossibility of conducting a comprehensive assessment of clinical status parameters and cognitive dysfunctions, as well as correlation of these parameters and assessment of dynamics of the immunocorrection. To achieve this goal the Scale of assessment of the criterion clinical symptoms of patients with ACA-HVI with CFS was used. It was shown that in mixed-HVI, the severity of symptoms exceeded the severity of symptoms of patients with mono-HVI and was 52.7 (43.1-62.2) and 38.0 (31.9-42.8) points, respectively (p > 0.05). Thus, it was found that patients suffering from mixed HVI have more pronounced, severe manifestations of CFS and aMCI, which are 1.5 times higher than similar manifestations in patients with mono-HVI, significantly reducing the quality of life of these patients, worsening their social adaptation.Prolonged persistence of herpes viruses in immune-compromised people creates conditions for constant antigenic stimulation and immune imbalance with the onset of secondary immunodeficiency or clinical manifestation of existing primary disorders in the immune system, which creates the prerequisites for the development of neuro-immuno-inflammatory changes in nervous system, followed by the formation of clinical manifestations of ME/CFS with different cognitive impairments that may be classified as aMCI.